Report on industrial immersion with Fearnleys Asia (Singapore) Pte Ltd - Wu, Mengxia. (2009)
The Industrial Immersion (II) is an essential part of Maritime Studies undergraduate curriculum. During the 10-week attachment, the industrial exposure should enable the student to apply the knowledge learnt in school, practice communication skills and build up the idea on professionalism. The student was supervised and guided by a supervisor from the attached organization as well as an II tutor from NTU. In this report, there will be a brief introduction to the company's profiles, structures and operations. Followed up will be the in-depth documentation of the 10-week attachment with job rotations among 5 departments. I will state the progress I have made during the past 10 weeks, by discussing my daily job functions, one important project I have completed. There are some special events and industrial exposures worth mentioning. Lastly, I would like to share some insights at the conclusion.